Implementasi Adjustable Frequency Menggunakan Protokol I^2 C pada Pulse Width Modulation Generator Berbasis Field Programmable Gate Array (FPGA) - Gandha, Gutama Indra (Teknik Elektro - Politeknik Negeri Semarang, 2017)
Pulse Width Modulation (PWM) has widely used in industrial and domestic applications. The advantages of the PWM utilization is low power loss in device switching process. It affects the device power consumption. The conventional PWM generation including the analog circuitry. However it has several disadvantages including high complexity, hard to modify and low flexibility. Microcontroller is an electronic device that has capabilities to generate PWM signal. The frequency of PWM signal generated by microcontroller is fixed or unchangeable.Â Many applications require PWM signal with adjustable frequency feature. The FPGA is a solution to resolve the problem. The Â interface has been used to provide the communication line between FPGA and other devices. The FPGA based- PWM generation has precision level and error by 94% and 6%.Keywords : field programmable gate array, pulse width modulation, IC Design Keyword